Eurozone bailouts and national democracy: Detachment or resilience?. (September 2019) - Schraff, Dominik; Schimmelfennig, Frank
How did the Eurozone bailouts affect national democracies? Recent research indicates strong citizen detachment due to the external constraints imposed by bailout programs on national autonomy. This paper re-examines the detachment thesis by broadening the view toward multiple dimensions of democracy and effect heterogeneity across time and space. Using the generalized synthetic control method, we find a negative effect of bailouts on satisfaction with democracy and turnout but show that effects vanish after several years and vary strongly across bailout cases. In addition, we find resilient attitudes and behaviors in spite of national democratic institutions that continue to deteriorate. These findings indicate that economic policy outcomes have a stronger influence on satisfaction with democracy and electoral turnout than the quality of the democratic process.